REKAYASA EKOLOGI PERTANAMAN CABAI DENGAN REFUGIA DALAM DEMONTRASI PLOT DIDESA PEMATANG GUNTUNG - Mayly, Syarifa; Misdawati, Misdawati; Hidayat, Benny (LPPM Universitas Bina Bangsa, 2024)
PKM Ecological Engineering Red chili planting with refugia is an appropriate technology implemented to overcome the problems of partners, namely farmer groups in Pematang Guntung Village, Serdang Bedagai Regency. Ecological Engineering with refugia plants is one of the control techniques in IPM with the aim of manipulating the ecosystem in the availability of natural enemies in a planting area so that pest attacks remain below the economic threshold. Ecological engineering in this activity aims to provide the availability of food from natural enemies found in red chili plantings so that red chili production is optimal, reducing pesticide use, cheap and environmentally friendly. The products produced are knowledge of integrated pest control (IPM) and refugia planting in red chili planting areas. This PKM is implemented in 2 stages, namely the training stage which lasts one day and the stage of making a demonstration plot for red chili planting carried out by farmer groups and mentoring. The refugia used in this PKM are chicken dung flowers, kenikir, zinnia sp flowers and babadotan weeds which were introduced to farmer group partners in Pematang Guntung Village, Serdang Bedagai Regency. The use of refugia plants has been proven to minimize the use of pesticides and also provide knowledge/educational tourism to students in Pematang Guntung Village, Serdang Bedagai Regency